COVID is fake; it’s a plandemic: a case study on the motivations of Filipino COVID-19 deniers’ information-seeking behavior - Buenavista, Ces Archae D.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2022)
The contamination brought by COVID-19 also spread in the information sphere through the infodemic brought by the spikes of information disorders during the pandemic, such as conspiracy theories proclaiming that COVID is fake; it is all planned, a plandemic. Due to an encounter with a COVID-19 denier, the researcher was inspired to explore the factors motivating the information-seeking behavior of Filipino COVID-19 deniers.

The literature says education or literacy defines information disorder vulnerability or conspiracy belief. However, recent studies show that this instance does not seem exclusively a consequence of education. This study used the Modified Comprehensive Model of Online Health Information Seeking to accommodate social media use and exposure to information disorders, truthiness, and distrust in authorities or credible media as factors motivating conspiracy belief.

This case study interviewed five (5) followers of Gising Maharlika TV, an independent media alternative propagating COVID denier perspectives. Their beliefs echo the popular COVID conspiracies mentioning Bill Gates, Big Pharma, and 5G. The results also show that the participants prefer sources with truthiness attributes and platforms “free from censorship.” They actively seek information in these spaces and are quick to avoid mainstream and credible sources. The study identified religiosity or spirituality and the Philippine government’s administration of the COVID-response as specific factors motivating vaccine disapproval and distrust in scientific and authoritative sources. This study concluded by pointing out the opportunity to establish discourse with the disinformed in understanding the mechanics of information disorders and formulating strategies for communicating scientific and reliable information effectively.
Thesis
Keywords: Information behavior; COVID-19 (Disease) -- Public opinion. -- Philippines; COVID-19 (Disease) -- Case studies. -- Philippines; Misinformation; Denialism